2022
DOI: 10.1007/s10798-022-09776-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of barriers, supports and gender gap in the choice of STEM studies in secondary education

Abstract: Society is more digitised than ever and there is an urgent need to train people in these sectors, where women are still under-represented. A quantitative descriptive, correlational and explanatory descriptive design was used to identify barriers, supports and gender gaps in Science, Technology, Engineering and Mathematics in Secondary Education by analysing the interest and perception of 1562 students and 432 teachers. Descriptive statistics, Chi-square and Lambda test and Crame’s V or Phi test were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…In Calvo, Epifanio, Estrade and Mas de les Valls (2022) a revision is exposed on gendered stereotypes in Engineering, Physics and Mathematics within the Spanish context. The individual and object-oriented work without a focus on its final benefit for the society is the dominant stereotype in Engineering, coinciding with the findings reported by Merayo and Ayuso (2022). In Sáinz et al (2020) it is found that social utility values associated with the STEM field and educators' encouragement where predominant factors for women compared to personal values and the role of family tradition and mass media for men.…”
Section: Literature Reviewsupporting
confidence: 75%
See 1 more Smart Citation
“…In Calvo, Epifanio, Estrade and Mas de les Valls (2022) a revision is exposed on gendered stereotypes in Engineering, Physics and Mathematics within the Spanish context. The individual and object-oriented work without a focus on its final benefit for the society is the dominant stereotype in Engineering, coinciding with the findings reported by Merayo and Ayuso (2022). In Sáinz et al (2020) it is found that social utility values associated with the STEM field and educators' encouragement where predominant factors for women compared to personal values and the role of family tradition and mass media for men.…”
Section: Literature Reviewsupporting
confidence: 75%
“…The cause of the lack of female students' enrolment in STEM degrees has been extensively studied. It is widely accepted that a multiplicity of constrains influence on the female students' enrolment decision, including the perception of a lesser ability in maths and ICT, a lower self-concept compared to their male counterparts, persistent gendered stereotypes in the society and the lack of female outstanding personalities, among others (Wang & Degol 2017, Sáinz, Fàbregues, Rodó-de-Zárate, Martínez-Cantos, Arroyo & Romano, 2020, Fernández-García, Torío-López, García-Pérez & Inda-Caro, 2019, Merayo & Ayuso 2022. In Calvo, Epifanio, Estrade and Mas de les Valls (2022) a revision is exposed on gendered stereotypes in Engineering, Physics and Mathematics within the Spanish context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the educational setting promotes gender equality in terms of learning opportunities and the development of practical skills, both male and female students possess an equal capacity to cultivate ACS. (Aldraiweesh & Alturki, 2023;De Prada et al, 2022;Guo et al, 2023;Hanisch & Eirdosh, 2023;Merayo & Ayuso, 2023;Qi et al, 2023;Tabassum & Nayak, 2021;Taylor, 2017;Zvavahera et al, 2023). Social, cultural, and value factors that change over time may also play a role in reducing gender differences in the development of action competencies in higher education institutions (Andersen & Smith, 2022;Balducci, 2023;Lundberg, 2020).…”
Section: Comparison Based On Gendermentioning
confidence: 99%
“…Since the STEM sector is expected to generate the highest demands for labor, 45% in 2022 5 and given that many institutions, companies, and organizations affirm that 'the future lies in digitally boosting the world's economies' 2 , there is a clear convergence between socioeconomic status and the gender gap in these disciplines.…”
Section: Introductionmentioning
confidence: 99%